Safety, Feasibility and Economic Analysis of Same Day Discharge Following Elective Percutaneous Coronary Intervention. Issue 16 (August 2022) - Hyasat, Kais; Femia, Giuseppe; Alzuhairi, Karam; Ha, Andrew; Kamand, Joseph; Hasche, Edmund; Rajaratnam, Rohan; Lo, Sidney; Almafragy, Hamid; Liou, Kevin; Chiha, Joseph; Asrress, Kaleab
Background: Advances in percutaneous coronary intervention (PCI) has made the possibility of facilitating same day discharge (SDD) of patients undergoing intervention. We sought to investigate the feasibility, safety and economic impact of such a service. Methods: We retrospectively collected data on all patients undergoing outpatient PCI at our institution over a 12-month period. We included in-hospital and 30-day major adverse cardiac events (MACE), vascular complications, acute kidney injury and any re-hospitalisations. We analysed the cost effectiveness of SDD compared to overnight admission post PCI and staged PCI following diagnostic angiography. Results: A total of 147 patients undergoing PCI with 129 patients deemed suitable for SDD (88%). Mean age was 65.7 years. Most patients had type C lesions (60.3%); including 4 chronic total occlusions (CTOs). At 30-day follow-up there were no MACE events (0%). There were 10 (7.8%) re-hospitalisations of which majority (70%) were non cardiac presentations. We also included cost analysis for an elective PCI with SDD, which equated to 2090 per patient (total of 269 610 for cohort). Elective PCI with an overnight admission was 4440 per patient (total of 572 760 for cohort), an additional 2350 per patient (total 303 150). Total cost of an angiogram followed by a staged PCI with an overnight stay was 4700 per patient (total 606 300). Conclusion: SDD is safe and feasible in the majority of patients that have elective coronary angiography that require PCI. SDD leads to a significant reduction in total cost and hospital stay of patients undergoing elective PCI.